IMPLEMENTASI LEGISLASI HAK-HAK ASASI MANUSIA DI INDONESIA - Manumpak Tampubolon (Universitas 17 Agustus 1945 Samarinda, 2014)
ABSTRACT From the analysis that has been done, it can be concluded that judicial organic laws strictly regulate back to the material of human rights contained in the Constitution of 1945. The reorganization is necessary because, as mandated by the undangdasar 1945 that the right to organize -hak it must first be regulated by law (article 28 of Law 1945). And in this case the laws that have been successfully made by the government are, among others: Law 48 of 2009 on the Principles of Judicial Power. Law 12 of 2012 on the National Education System. Law No.21 of 1982 on Basic Provisions Press. Law No. 8 of 1985 on Social Organization. Act 3 of 1985 on Political Parties and Golkar. Law No. 13 of 2003 on Manpower. Decree of the Minister of Manpower No. KEP-150 / MEN / 2000 on the Implementation Guidelines for layoffs. Law 13 of 2006 on the Protection of Witnesses and Victims and many others. In rearranging the material of human rights law that was set to strict, because the settings are concepts that are not clearly understanding (Act 21 of 1982). Besides, there is also a rigid formula (Act 2 of 1989) which can make the private sector reluctant to participate in the government in an effort to ease the task of educating the nation. Also the presence of a strange provision in the Law 22 of 1957 for workers who are organizing an action should give them know in advance to employers.